(3aJM GdhUjO aj TQM GdbUjO (B( (3GdTGWHjI (B)s - (3CHh GdMSf GdSNGhi Ydj Hf eMeO Hf YHO GdUeOs; (3GdTGWHj GdebQF GdVQjQ , CHh eMeO,J (B590 (3g` s ((3CMeO Hf YKeGf Hf GdLfRi s)
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje bGd GdTjN Gdabjg GdEeGe CHh GdbSe GHf ajQg GdOYjfi GdTGWHi QVi Gddg Yfg bUjOI edbHI HMQR GdCeGfi hhLg GdJgGfi hTQMgG GdTjN CHh GdMSf Ydi eMeO YHO GdUeO GdSNGhi s
(3BNQgG (B:s
(3Ci JLYdgG PGJ faGSg heYfi Pdc Cfg EPG fXegG aMaXgG ef dGYde dg s
(3GdfSNI HgG MhGTs
(3MQR GdCeGfi GdeSei HGdbUjOI GdTGWHjIs
(3fSNI KGfjI s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3JHUQI GdYfhGf (B:s
Keywords: (3GdbQGAGJ hGdJLhjOs